Conceptual foundations of I. Ya. Yakovlev's didactics and modern technologies of independent work of students in a pedagogical university - Lyudmila N. Danilova (Развитие образования)
The article is devoted to the study of the conceptual foundations of I.Ya. Yakovlev's didactics. The work presents an analytical description of the technologies of independent work, self-development, self-education in the pedagogical system of the educator of the Chuvash people. Based on the content of federal state educational standards of higher education, the author proves the relevance of I.Ya. Yakovlev's didactic system in modern conditions of the implementation of the "Core of Higher Pedagogical Education", their innovative nature, the effectiveness of the organization of the educational process in the Simbirsk Chuvash Teachers' School. The work presents the results of the analysis of modern curricula in the direction of training "Psychology and Pedagogy of Preschool Education" for the presentation of a description of technologies and the amount of time for completing assignments for independent work. The study of I.Ya. Yakovlev's didactic system is built taking into account the knowledge, ethnocultural, personological paradigms and on the principles of consistency and competence. The results of the study, obtained on the basis of theoretical analysis of pedagogical literature and normative regulators of education, have a methodological nature, are consonant with the requirements for the results of the formation of universal, general professional and professional competencies. The author presented a substantive analysis of the author's and advanced technologies for the 18th century for organizing the classroom and extracurricular work of students: reading, retelling, taking notes on pedagogical literature, research, project, essay-reasoning, developing logic and critical thinking. The described technologies require reconstruction in new socio-cultural conditions, they can be recommended for use in the educational process of a modern university.